Scrum-Based Mobile Application Development for Patient Satisfaction Assessment in Class 'B' Hospitals in Padang - Nabilla, Regina; Dian, Yulef; Idris, Iswandi (The Indonesian Journal of Computer Science, 2024)
The assessment of patient satisfaction is a critical aspect of healthcare services, providing valuable insights into the quality of care and service delivery. In Padang's Class "B" hospital, traditional satisfaction assessment methods are inefficient and time-consuming. This research explores the implementation of the Scrum methodology in the development of a mobile application for real-time patient satisfaction assessment. The objective is to enhance feedback collection, improve service quality, and provide hospital management with actionable insights. The mobile application allows patients to rate services on various parameters instantly, enabling quicker responses and continuous improvement of hospital operations. This study discusses the technical implementation, the advantages of using Scrum in the development process, and the potential impact on service quality in the hospital